Journal of Mathematics in Industry - Günther, Michael
The Journal of Mathematics in Industry is a high-quality journal that brings together research on developments in mathematics for industrial applications, including both methods and the computational challenges they entail. Here, industry is understood as any activity of economic and/or social value. As such, "mathematics in industry" concerns the field as it actually improves industrial processes and helps to master the major challenges presented by cost and ecological issues. By publishing high-quality, innovative articles, it serves as an essential resource for academic researchers and practitioners alike. At the same time, it provides a common platform for scholars interested in precisely those types of mathematics needed in concrete industrial applications, and articles focusing on the interaction of academia and industry are preferred. In terms of theory, the journal seeks articles with demonstrable mathematical developments motivated by problems of modern industry. With regard to computational aspects, it publishes works introducing new methods and algorithms that represent significant improvements on the existing state of the art of modern numerical and simulations methods. The journal welcomes proposals for special issues on carefully selected topics, reflecting the trends of research and development in the broad area of mathematics in industry. Insightful survey articles may also be submitted for publication by invitation.